ANALISIS PENGARUH TATA KELOLA PERUSAHAAN DAN PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN - B Ivanno Eka P; Dul Muid (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effects of corporate governance and tax avoidance toward the value of a company that a company may undertake.The sample in this study consists of 60 manufacturing companies listed on the Indonesia Stock Exchange with a total of 138 observations in the period 2014-2015. The sample is selected by purposive sampling method. Data analysis was performed with data quality testing,  classical assumption testing, and hypothesis testing with multiple linear regression model.This study shows that good corporate governance has a positive and significant impact on company value. While tax evasion has a negative and significant influence on the value of the company.